Phytochemical Analysis and Pharmacological Properties of Epipremnum pinnatum (L.) Fruit Extracts - Villar-Cabalhin, Mary Annilyn L.; Aguilar, Ma. Ariane Lou C.; Renomeron, Jill Daryl A.; Fuentes, Rolly G. (HAYATI Journal of Biosciences, 2025)
Epipremnum pinnatum (L.) Engl., belonging to the family Araceae, is a medicinal plant used by locals in many Asian countries to treat common ailments such as wounds and pain. In this study, the different parts of the fruits -peel, core, and kernels were analyzed for their phytochemicals and antioxidant potentials. Initial phytochemical investigation revealed that flavonoids, polyphenols, and sterols were found in all parts. Terpenoids were found in the core and peel extracts, while cardiac glycosides were found in the core and kernel extracts. The peel extracts were found to have the highest flavonoid content (308.9±19.2 mg quercetin equivalent per g fresh wt sample). It also exhibited the highest total antioxidant activity (EC50 = 23.1±4.2 ppm) among the three extracts, which is next to the activity of ascorbic acid (EC50 = 4.6±1.6 ppm) using the phosphomolybdate method. It also gave the highest DPPH-free radical scavenging activity (EC50 = 41.9±2.6 ppm) among the three extracts but lower activity than the ascorbic acid (EC50 = 1.1±0.5 ppm). At 200 ppm, the peel extracts exhibited a profound inhibitory effect (>50%) on the melanin production in zebrafish embryos. But, at this concentration, the peel extracts were also found to be toxic to the embryo, with 43% mortality. However, the extract did not exhibit antibacterial properties against E. coli and S. aureus. These results suggest the potential of the fruit parts, particularly the peel, as a source of natural compounds with pharmacological importance.